PENGARUH MINUMAN KUNYIT ASAM TERHADAP PENURUNAN DISMENORHEA PADA REMAJA PUTRI PONDOK TAHFIZ AL-QURAN NURUL QALBI - Trya Mia Intani; Delfi Yulita; Radian Ilmaskal (GoAcademica Research dan Publishing, 2022)
The purpose of this study was to determine the effect of sour turmeric drinks on reducing dysmenorrhea in young women. The method used in this research is Quasi experimental pre-post test. The sample in this study were young women who experienced dysmenorrhea at Pondok Tahfiz Al Quran Nurul Qalbi, totaling 30 respondents, 15 for the control group and 15 for the intervention group. The data analysis used was Univariate and Bivariate, where bivariate analysis used the Independent t test. In the intervention group, before being given the tamarind drink, 53.4% experienced moderate menstrual pain and after being given the tamarind drink, it decreased to 80% experiencing mild pain. In the control group, before being given the tamarind turmeric drink, it was found that 46.7% experienced mild pain and increased to 53.3% experienced moderate menstrual pain without being given the tamarind turmeric drink. Based on statistical tests, there is an effect of sour turmeric drinks on reducing dysmenorrhea in young women with a p value = 0.047. Tamarind turmeric drink is one way of non-pharmacological therapy that can be done to reduce menstrual pain (dysmenorhea) in young women.